Evaluation of the level of professional socialization of postgraduate nursing students - Sabery, Mahdieh; Ashktorab, Tahereh; Heydarikhayat, Nastaran (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: Professional socialization is an important issue in nursing. This process creates a mechanism that group members think and act the same and finally will control over their actions. With growing expectation from nurses omits exits professional socialization dimensions such as independency, problem solving, responsibility, conducting research and competency of care delivery. Nevertheless, there are fewer problems with professionalism in nurse specialists and the levels of patient’s satisfaction of delivered services are increased, so the aim of this study is to evaluate the level of professional socialization of nursing student postgraduate degree. Materials and Methods: A descriptive study in Shahid Beheshti School of nursing and midwifery in 2015 was conducted. Population of study was the MSc nursing student. Census Sampling was conducted and all students who wish to participate in the study were enrolled. The questionnaire was an instrument which was designed in a previous PhD in nursing dissertation. Finding: The range of participant’s age was 23 to 45 with mean ± SD 30.81±6.1 years. 79.4% of study units were female. The majority of students were married and live in urban area. Mean score of professional socialization of nursing students was 212±22.2 and it was ranged from 157 to 269. Conclusion: Based on the scores of professional socialization of MSc nursing students, it was in a high level. The score was equal to the level of proficient and expert at Benner’s stages of clinical competence. It can be recommended that to make the learning of professional development and socialization from undergraduate level more effective the education in postgraduate degrees should be facilities. More collaboration between university and clinical environment should be provided. Keywords: Professionalism; Socialization; Nursing; Education; Education, Nursing, Postgraduate